Measuring the Parameters of Maximum Muscle Strength, Muscle Mass, Muscle Damage in Active Adult Males after Low–Load High–Repetition with High–Load Low–Repetition Resistance Training - Subagio, Irmantara; Samudra, Fajar Eka; Pranoto, Adi; Kartiko, Dwi Cahyo; Wiriawan, Oce; Suyoko, Andri; Primanata, Dani; Orhan, Bekir Erhan (Physical Education Theory and Methodology, 2025)
Objectives. This study aimed to evaluate the effects of high-load, low-repetition (HLLR) and low-load, high-repetition (LLHR) resistance training protocols on muscle strength, muscle mass, and muscle damage in active adult males. Materials and methods. This quasi-experimental study involved 28 active adult males aged 18-22 years with a body mass index of 19-23 kg/m2 selected to actively participate in the study and given HLLR and LLHR interventions with a frequency of 3x/week for 4 weeks. Data collection was carried out by assessing maximum muscle strength, muscle mass, and muscle damage between baseline (pre) and week 4 (post). Statistical analysis used an independent sample t-test, with a significance level of 95%. Results. There were significant differences between HLLR and LLHR interventions in max strength lower body (effect size (ES): 1.024), max strength upper body (ES: 1.241), and muscle mass (ES: 1.184) (p < 0.05). Meanwhile, CK activity was found to be significantly reduced in LLHR compared to HLLR (ES: 0.828) (p < 0.05). Conclusions. This study demonstrated that high-load, low-repetition (HLLR) training was more effective for increasing muscle strength and muscle mass, while low-load, high-repetition (LLHR) training reduced muscle damage, as indicated by lower creatine kinase levels.